Food Politics and Counter-Hegemonic Assertion in Indian University Campuses. (July 2016) - Pathania, Gaurav J.
Recently, heated debates concerning food politics have erupted at some of the most prestigious institutes of higher education in India. Students demand inclusion of beef and other meat in their hostel food menu, claiming hostel canteens represent only 'mainstream' Hindu culture. To boycott this culture and instil consciousness of their cosmopolitan life-world, they organise campus 'Beef Festivals' and publicly idolise so-called 'demons' of Hindu mythology. Using a Gramscian framework, this article explores the activism of marginalised students as counter-hegemonic and critically examines the ideological standpoints involved. As university spaces become significant sites to reinvent caste identities, we see that in their counter-hegemonic struggles, marginalised students employ the same tools and symbols of meat and myth as their opponents. It is argued that this strategy ultimately risks contradicting the goal of their activism and may block broader visions of an equal and just society.